“Factors that influence the channel switching intention of the consumers in Bangladesh towards online grocery shopping: the moderating effect of the fear of Covid-19” - Furkan, Mohammed (2022)
The purpose of this study is to investigate the influence of the factors, such as perceived usefulness, perceived ease of use, price-search intentions and perceived risk on the channel switching intention of the consumers towards using online grocery shopping. The study also aims to examine the influence of consumers fear of COVID-19 on the interaction between the factors and the intention of the consumers to switch their grocery shopping channels. The research is a quantitative analysis using primary data, obtained by receiving responses to online questionnaire. Participants were recruited using snowball sampling, and were restricted to Bangladeshi nationals only. The study successfully confirmed the two hypotheses of TAM. The influence of perceived usefulness on channel switching intention and the influence of perceived ease of use on the perceived usefulness of using online grocery shopping was found to be statistically significant in this study. The study also finds that the price-search intention was a significant factor in predicting the consumers’ intention of switching channels. The results can be used by marketers and online retailers of Bangladesh to develop improved strategies to attract consumers towards using online grocery shopping. The results and limitations can also be used by future researchers to enhance the quality of their study.